2021
DOI: 10.1371/journal.pgen.1009538
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide investigation of stop codon readthrough in Saccharomyces cerevisiae

Abstract: Translation of mRNA into a polypeptide is terminated when the release factor eRF1 recognizes a UAA, UAG, or UGA stop codon in the ribosomal A site and stimulates nascent peptide release. However, stop codon readthrough can occur when a near-cognate tRNA outcompetes eRF1 in decoding the stop codon, resulting in the continuation of the elongation phase of protein synthesis. At the end of a conventional mRNA coding region, readthrough allows translation into the mRNA 3’-UTR. Previous studies with reporter systems… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 67 publications
1
31
0
Order By: Relevance
“…screened reporter libraries with six randomized nucleotides 5′ of UAG and concluded that neither tRNA identity nor amino acid chemical properties influence termination efficiency ( 64 ). Instead they proposed that two 5′ adenines are major determinants of termination efficiency although a recent transcriptome-wide readthrough study in which eRF1 levels were reduced found no such bias ( 65 ). One study using a mouse cell line to monitor readthrough, concluded that neither the identity of the terminal amino acid nor the P-site codon frequency affected termination efficiency ( 66 ).…”
Section: Resultsmentioning
confidence: 99%
“…screened reporter libraries with six randomized nucleotides 5′ of UAG and concluded that neither tRNA identity nor amino acid chemical properties influence termination efficiency ( 64 ). Instead they proposed that two 5′ adenines are major determinants of termination efficiency although a recent transcriptome-wide readthrough study in which eRF1 levels were reduced found no such bias ( 65 ). One study using a mouse cell line to monitor readthrough, concluded that neither the identity of the terminal amino acid nor the P-site codon frequency affected termination efficiency ( 66 ).…”
Section: Resultsmentioning
confidence: 99%
“…Poly(A) selected mRNA libraries were mapped to an S. cerevisiae transcriptome reference 32 , which contains both pre- and post-spliced mRNA references (https://github.com/Jacobson-Lab/yeast_transcriptome_v5). Reads were aligned using Minimap2 33 in a splice-aware fashion with specific parameters (minimap2 -ax splice -uf -k14).…”
Section: Methodsmentioning
confidence: 99%
“…RNA-seq and ribosome profiling reads were aligned to a yeast transcriptome (available at ) using bowtie ( Langmead et al 2009 ), and transcript abundance was determined using RSEM ( Li and Dewey 2011 ), as described previously ( Mangkalaphiban et al 2021 ). For intron-containing genes, spliced (“mRNA”) and unspliced (“pre-mRNA”) isoforms were indexed as separate entries.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, reads arising from UPF factor transcripts were discarded from these and all subsequent ribosome profiling libraries analyzed. PCR duplicates identified via the 4N barcodes on either side of the read were removed ( Mangkalaphiban et al 2021 ). Read processing statistics for ribosome profiling libraries are provided in Supplemental Table S1 .…”
Section: Methodsmentioning
confidence: 99%